Deciphering the physiological response of Escherichia coli under high ATP demand. Issue 12 (20th December 2021) - Boecker, Simon; Slaviero, Giulia; Schramm, Thorben; Szymanski, Witold; Steuer, Ralf; Link, Hannes; Klamt, Steffen
Abstract: One long‐standing question in microbiology is how microbes buffer perturbations in energy metabolism. In this study, we systematically analyzed the impact of different levels of ATP demand in Escherichia coli under various conditions (aerobic and anaerobic, with and without cell growth). One key finding is that, under all conditions tested, the glucose uptake increases with rising ATP demand, but only to a critical level beyond which it drops markedly, even below wild‐type levels. Focusing on anaerobic growth and using metabolomics and proteomics data in combination with a kinetic model, we show that this biphasic behavior is induced by the dual dependency of the phosphofructokinase on ATP (substrate) and ADP (allosteric activator). This mechanism buffers increased ATP demands by a higher glycolytic flux but, as shown herein, it collapses under very low ATP concentrations. Model analysis also revealed two major rate‐controlling steps in the glycolysis under high ATP demand, which could be confirmed experimentally. Our results provide new insights on fundamental mechanisms of bacterial energy metabolism and guide the rational engineering of highly productive cell factories. Synopsis: A systematic analysis of the impact of different levels of ATP demand on E. coli under various conditions reveals a biphasic response curve of the glucose uptake rate with respect to increasing ATP demand. E. coli strains with varying ATP demand were generated by overexpressing the F1 ‐ATPase encoding genes with different expression strengths. Under all conditions tested, E. coli can buffer increased ATP demand by elevating the glucose uptake rate, but only to a critical point, beyond which glucose consumption drops markedly. A kinetic model as well as metabolomic and proteomic data reveal that the dual dependency of the phosphofructokinase on ATP (substrate) and ADP (allosteric activator) causes this biphasic behavior and leads to a collapse under very high ATP demand. The results provide important insights into the fundamental mechanisms of bacterial energy metabolism and may guide the rational engineering of highly productive cell factories. Abstract : A systematic analysis of the impact of different levels of ATP demand on E. coli under various conditions reveals a biphasic response curve of the glucose uptake rate with respect to increasing ATP demand.